Economic Geography and Regional Growth: An Empirical Evidence From Greece - Elias Kourliouros; George Korres; Emmanuel Marmaras; George Tsobanoglou (European Regional Science Association (ERSA), 2006)
There is a huge literature regarding the main determinants and sources of economic growth. Most of the recent work emphasizes on the role of knowledge, and innovation activities typically produced by a specific sector of the economy, and furthermore in the role of entrepreneurship and analysing the implications and the importance for economic growth. Moreover, the socio-economic and public policies aimi to distinguish the determining factors of growth, in order to enhance the regional cohesion and the convergence process. Much of the recent work on regional growth can be viewed as refining the basic economic insights of economic geography. There are two principal theories of why growth rates are differ, the first is the theory of comparative advantage and the second is the theory of increasing returns to scale. This paper attempts to examine the main sources of regional growth through an inter-and intra sectoral analysis. In particular, the paper attempts to investigate through an empirical inter-comparison study using statistical-data from several Greek regions, the determinant sectoral factors and the implications to growth process. We also employ the empirical non-parametric analysis. We find support for the existence of economic geography effects in several manufacturing sectors and moreover we find that these effects are economically very significant.
Keywords: 330